2017
DOI: 10.1007/s40268-016-0165-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Amikacin Pharmacokinetics and Pharmacodynamics for Optimal Initial Dosing Regimen

Abstract: Amikacin has been one of the important antimicrobial agents against Gram-negative pathogens. However, there is discrepancy regarding the amikacin initial dosage, with some reports recently recommending ≥25 mg/kg and others the conventional dosage (15–20 mg/kg). Hence, we evaluated the optimal initial dosing regimen of amikacin. Pharmacokinetic (PK) parameters were estimated using a population PK analysis. The pharmacodynamic (PD) target was a ratio of ≥8 between the concentration achieved 1 h after beginning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 22 publications
1
37
1
2
Order By: Relevance
“…The first antibiotic exposure tested in the HF model simulated the plasma concentrations of patients receiving 15 mg/kg amikacin once a day ( Kato et al, 2017 ) and/or 1 g vancomycin every 12 h ( Nicasio et al, 2012 ). Since the free plasma drug concentration is known to be one of the best surrogates of the concentration at the site of infection ( Liu et al, 2002 ), we exposed the bacteria in the HF model to concentrations similar to the free plasma concentrations obtained in patients after administration of the above dosing regimens.…”
Section: Methodsmentioning
confidence: 99%
“…The first antibiotic exposure tested in the HF model simulated the plasma concentrations of patients receiving 15 mg/kg amikacin once a day ( Kato et al, 2017 ) and/or 1 g vancomycin every 12 h ( Nicasio et al, 2012 ). Since the free plasma drug concentration is known to be one of the best surrogates of the concentration at the site of infection ( Liu et al, 2002 ), we exposed the bacteria in the HF model to concentrations similar to the free plasma concentrations obtained in patients after administration of the above dosing regimens.…”
Section: Methodsmentioning
confidence: 99%
“…As with other drugs used in the treatment of CRE infections, the adequacy of the generally recommended dosage for aminoglycosides (5 to 7 mg/kg/day for gentamicin and tobramycin; 15 to 20 mg/kg/day for amikacin) has also been questioned. A study of patients with severe sepsis or septic shock who were treated with amikacin at 25 mg/kg/day showed that only 70% reached peak concentrations of Ͼ64 mg/liter, which would be Ն8 times the susceptibility breakpoint against Enterobacteriaceae according to EUCAST (8 mg/liter) (316); the same dose, however, should be enough for isolates with a MIC of 4 mg/liter to reach the same target (317). An initial dose of 2,500 mg followed by therapeutic drug monitoring has been suggested for patients with body weights of Ͼ40 kg (318,319).…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…As a consequence of glomerular hyper filtration, augmented renal clearance refers to enhanced excretion of hydrophilic compounds (circulating metabolites, toxins, waste products, and drugs including amikacin) in comparison to renal baseline function. There is a variety of clinical conditions leading to augmented renal clearance including sepsis, trauma, particularly burn injury, pancreatitis, autoimmune disorders, ischemia, and major surgery [11,13]. Often these conditions also lead to increased apparent volume of distribution, providing an additional Factor potentially contributing to insufficient antimicrobial concentrations.…”
Section: Renal Function Of Patient Populationmentioning
confidence: 99%
“…At the hospital level, the amino glycoside amikacin has been one of the most frequently prescribed antimicrobial agents against Gram-negative and multidrug resistant pathogens such as Pseudomonas aeruginosa [10,11]. Although widespread used, amikacin exhibits a narrow therapeutic plasma index, potential nephro-and ototoxic side effects and wide intra-and inter-individual variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation